Updating the files: Understanding the public service through storytelling and narrative - Mulreany Michael; O’Brien Denis (Administration)
In this article, we reconsider our 2011 book Lord of the files: Working for the government, which was the first of its kind to collect written sources from hundreds of writers inside and outside the public service on the realities and complexities of Irish public service life. Its portrayal of institutional life, state administration and the delivery of public services as they play out within the values expected of public servants aimed to provide a rounded understanding of what is conventionally known as ‘working for the government’.